Psychopathology in parents of children with autism spectrum disorder: A systematic review and meta-analysis of prevalence. (January 2020) - Schnabel, Alexandra; Youssef, George J; Hallford, David J; Hartley, Eliza J; McGillivray, Jane A; Stewart, Michelle; Forbes, David; Austin, David W
Parents of children with autism spectrum disorder appear to experience high levels of psychological distress, yet little is known about the prevalence of psychological disorders in this population. The aim of this systematic review and meta-analysis was to estimate the proportion of these parents who experience clinically significant psychopathology. Articles reporting proportions of psychological disorders in a sample of parents of children with autism spectrum disorder were located. The initial search returned 25, 988 articles. Thirty-one studies with a total sample of 9208 parents were included in the final review. The median meta-analytic proportions were 31% (95% confidence interval = [24%, 38%]) for depressive disorders, 33% (95% confidence interval = [20%, 48%]) for anxiety disorders, 10% (95% confidence interval = [1%, 41%]) for obsessive-compulsive disorder, 4% (95% confidence interval = [0%, 22%]) for personality disorders, 2% (95% confidence interval = [1%, 4%]) for alcohol and substance use disorders and 1% (95% confidence interval = [0%, 5%]) for schizophrenia spectrum disorders. Significant heterogeneity was detected in these categories. Further research is needed to gain more insight into variables that may moderate parental psychopathology. This review and meta-analysis is the first to provide prevalence estimates of psychological disorders in parents of children with autism spectrum disorder.